Prevalence of Autism risk among children undergoing regular Psychophysical Development Screening in Kazakhstan - Karina Nukeshtayeva; Bauyrzhan Omarkulov; Marina Lyubchenko; Nailya Delellis; Olzhas Zhamantayev; Zhaniya Dauletkaliyeva; Gulmira Zhanalina; Nurzhamal Shintayeva; Gulden Karshalova; Maira Kenzhekeyeva (Elsevier, 2024)
Background: Information about the situation with autism in Kazakhstan is extremely limited due to the lack of research on autism in both Kazakhstan and Central Asia. The prevalence of autism spectrum disorder risk among young children during routine screening was assessed using the M-CHAT-R/F tool. Methods: This study took place in the offices of pediatric neurologists and family doctors in three primary healthcare organizations in the Karaganda, Kazakhstan. The researchers offered participation in the study and M-CHAT-R checklist completion during visits by parents and children to pediatric neurologists and family doctors for the purpose of screening for psychophysical development. Linear regression analysis was used to determine risk factors for the development of autism spectrum disorder. Results: The results of an analysis of 526 study participants showed the prevalence of high-risk autism spectrum disorders to be 27.4 %. Factors associated with a high risk of autism spectrum disorder in this study were child age, gender, parental age, and a diagnosis of developmental disorder. Conclusions: The use of specific tools to screen for developmental disorders by primary care organizations is recommended. Primary care providers have regular contact with children before they reach school age and can provide family-centered, comprehensive, and coordinated care, including more comprehensive medical assessments.